2014
DOI: 10.1097/ta.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow motor scale alone is equivalent to Glasgow Coma Scale at identifying children at risk for serious traumatic brain injury

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…In adults with severe head injuries, the motor component of the GCS has been shown to be the component most strongly correlated with injury severity and outcomes . One small trauma registry study of 96 children up to 18 years old with moderate‐to‐severe head injuries demonstrated similar findings, as did two more recent retrospective reviews of seriously injured children . In a previous study of children with mostly minor head trauma, however, the verbal and eye components were somewhat more important than the motor component consistently, but this did not achieve statistical significance .…”
Section: Discussionmentioning
confidence: 90%
“…In adults with severe head injuries, the motor component of the GCS has been shown to be the component most strongly correlated with injury severity and outcomes . One small trauma registry study of 96 children up to 18 years old with moderate‐to‐severe head injuries demonstrated similar findings, as did two more recent retrospective reviews of seriously injured children . In a previous study of children with mostly minor head trauma, however, the verbal and eye components were somewhat more important than the motor component consistently, but this did not achieve statistical significance .…”
Section: Discussionmentioning
confidence: 90%
“…Assessment of the neurologic status (D) includes a careful evaluation of the patient’s level of consciousness using the Glasgow Coma Scale (GCS), the assessment of pupillary size and reaction, lateralizing signs and spinal cord injury level. The GCS, with its pediatric version for preverbal children (Supplementary online Appendix), is predictive of patient outcome, particularly the best motor response [ 12 ]. The total GCS and its eye, vocal and motor components, as well as pupillary size and reaction should be carefully documented in the clinical notes at each assessment in order to promptly identify any neurological deterioration or improvement.…”
Section: Recommendationsmentioning
confidence: 99%
“…We registered the same vital parameters for children. GCS is validated for use in children with the same standards as adults and used in this study [55]. We dichotomised SBP, HR and RR as normal or abnormal according to the Norwegian modified paediatric early warning score [56][57][58][59], and defined SI as abnormal if > 1.22 up to six years, > 1.0 between six and twelve years and > 0.9 above twelve years [60,61].…”
Section: Vital Parameters (Children)mentioning
confidence: 99%